Bioecology and Entomophagus of the Coccidia Family - Tillavoldiyeva Umidaxon; Shukrullayeva Munisa; Nigmanova Laylo (Scientific Trends, 2023)
This article provides information about the family of cockcids, one of the main begging pests of fruit gardens, as well as their species found in the republic, causing more damage to purple, California, and Central Asian comma thyroid thyroids, as well as the type content of the main entomophagus of these pests.
Keywords: beggar, garden,entomophagus, cockeyed, Chilocorus bipustulatus